2018
DOI: 10.1002/ijc.31411
|View full text |Cite
|
Sign up to set email alerts
|

Time from breast cancer diagnosis to therapeutic surgery and breast cancer prognosis: A population‐based cohort study

Abstract: Theoretically, time from breast cancer diagnosis to therapeutic surgery should affect survival. However, it is unclear whether this holds true in a modern healthcare setting in which breast cancer surgery is carried out within weeks to months of diagnosis. This is a population- and register-based study of all women diagnosed with invasive breast cancer in the Stockholm-Gotland healthcare region in Sweden, 2001-2008, and who were initially operated. Follow-up of vital status ended 2014. 7,017 women were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 39 publications
0
45
0
Order By: Relevance
“…OS was reported in twelve breast cancer studies; including eleven analyses of non-stage specific (multiple stage) disease 29 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ; four of stage I only disease 39 , 41 , 42 , 45 ; four of stage II only disease 39 , 41 , 42 , 45 ; and three of stage III only disease. 39 , 41 , 42 Sample sizes ranged from 1702 to 420,792 with a mean of 176,657 patients.…”
Section: Resultsmentioning
confidence: 99%
“…OS was reported in twelve breast cancer studies; including eleven analyses of non-stage specific (multiple stage) disease 29 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ; four of stage I only disease 39 , 41 , 42 , 45 ; four of stage II only disease 39 , 41 , 42 , 45 ; and three of stage III only disease. 39 , 41 , 42 Sample sizes ranged from 1702 to 420,792 with a mean of 176,657 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, Roland et al found no association between pretreatment wait time and survival [23]. A significant correlation between preoperative wait time and survival has been demonstrated in only breast cancer [4][5][6][7]. Bleicher et al reported that OS worsened with increasing preoperative wait time in five intervals (≤ 30, 31-60, 61-90, 91-120, and 121-180 days) [4].…”
Section: Discussionmentioning
confidence: 99%
“…Bleicher et al reported that OS worsened with increasing preoperative wait time in five intervals (≤ 30, 31-60, 61-90, 91-120, and 121-180 days) [4]. Eriksson et al reported a linear association between preoperative wait time and survival [5]. Hence, there are varying results with regard to the association between preoperative wait time and survival among cancer types, and this is probably because of different tumor characteristics and different treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most anxiety-provoking time for patients is the period from diagnosis to treatment initiation [4]. Moreover, previous studies [1,3,10,16] have suggested the length of the interval between diagnosis and surgery could affect the survival outcomes in early stage breast cancer. Thus, patients with early stage breast cancer should receive surgery as soon as possible.…”
Section: Daily Medical Treatments Of Cancer Patients Have Been Affectmentioning
confidence: 99%